1997
DOI: 10.1074/jbc.272.25.15898
|View full text |Cite
|
Sign up to set email alerts
|

A Plasma Membrane Sucrose-binding Protein That Mediates Sucrose Uptake Shares Structural and Sequence Similarity with Seed Storage Proteins but Remains Functionally Distinct

Abstract: Photoaffinity labeling of a soybean cotyledon membrane fraction identified a sucrose-binding protein (SBP). Subsequent studies have shown that the SBP is a unique plasma membrane protein that mediates the linear uptake of sucrose in the presence of up to 30 mM external sucrose when ectopically expressed in yeast. Analysis of the SBP-deduced amino acid sequence indicates it lacks sequence similarity with other known transport proteins. Data presented here, however, indicate that the SBP shares significant seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…The primary sequence of SBP has 20±37% identity and 44±61% similarity with the vicilin-class proteins (Overvoorde et al, 1997). This indicates that the tertiary structure of SBP is closely related to those of canavalin and phaseolin and, as shown below, the potential of SBP subunits to assemble into trimers has also been assessed by model building.…”
Section: Sbp Modelmentioning
confidence: 91%
See 2 more Smart Citations
“…The primary sequence of SBP has 20±37% identity and 44±61% similarity with the vicilin-class proteins (Overvoorde et al, 1997). This indicates that the tertiary structure of SBP is closely related to those of canavalin and phaseolin and, as shown below, the potential of SBP subunits to assemble into trimers has also been assessed by model building.…”
Section: Sbp Modelmentioning
confidence: 91%
“…The model of phaseolin was obtained from the PDB (entry 2phl). According to the sequence alignment of Overvoorde et al (1997), also shown in Fig. 3, the polypeptide templates of residues 46±222, 246±321 and 332±421 were extracted from the re®ned cubic model of canavalin.…”
Section: Homology Modeling and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now considered likely that such a His cluster, together with an adjacent conserved Glu, may be the binding site for an Mn 2ϩ ion recently found to be the metal present in OXO, at least in those isolated from cereals (39,238,239). A similar combination of modelling and experimental approaches could be made using the structural data from the sugar-binding domain of the bacterial AraC transcription factor (270) and the sequence data from SBP (bicupins) from higher plants (40,219) in order to identify ligands specifically involved in the binding of either mono-or disaccharides in these subgroups.…”
Section: Structural Aspects Of Cupinsmentioning
confidence: 99%
“…In M. truncatula, the protein was found only in cotyledons, again perhaps in preparation for the developmental shift to photosynthesis. Two other binding proteins were identified: P54 and a vicilin-related seed protein that possibly functions in Suc binding (Overvoorde et al, 1997). In pea, P54 undergoes further maturation into P16, a possible participant in chromatin condensation induced by dehydration (Castillo et al, 2000), whereas in M. truncatula, the protein seems not to be further processed and presumably only acts in Suc binding.…”
Section: Binding Proteinsmentioning
confidence: 99%